The Influence of Sales Growth and Operational Efficiency On Financial Performance (A Study Of The Pharmaceutical Subsector Listed On The Indonesia Stock Exchange For The 2019–2023 Period) - Muswanto, Stephanie Immanuel; Aisyaturrahmi, Aisyaturrahmi (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the effect of sales growth and operational efficiency on financial performance in pharmaceutical subsector companies listed on the Indonesia Stock Exchange for the 2019–2023 period. Financial performance is measured using Return on Assets (ROA), while sales growth and operational efficiency are used as independent variables. This study also includes leverage, liquidity, and company size as control variables. This study uses a quantitative approach using multiple linear regression analysis techniques. The research data were obtained from the financial reports of pharmaceutical subsector companies published on the Indonesia Stock Exchange during the study period. The results show that sales growth and operational efficiency significantly influence company financial performance. Furthermore, the control variables leverage, liquidity, and company size also show a significant influence on financial performance. These findings indicate that a company's financial performance is influenced not only by sales growth but also by the company's ability to manage its operational activities and financial structure. Therefore, companies need to optimize sales and operational activity management to improve financial performance sustainably.